2010
DOI: 10.1901/jaba.2010.43-155
|View full text |Cite
|
Sign up to set email alerts
|

Recent Studies on Feeding Problems in Children With Autism

Abstract: This paper reviews recent studies on behavioral interventions for children with autism and feeding problems. The applicability of interventions that have been tested with other populations of children with feeding problems is discussed, as well as directions for future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 31 publications
(40 reference statements)
4
36
0
5
Order By: Relevance
“…The findings have shown that children with ASD were more likely to exhibit restrictive and inflexible eating behaviors, eat continually throughout the day instead of during specific mealtimes, resist sitting at the table, and throw or dump food during mealtimes compared to children who are typically developing (Koegel et al, 2012;Matson et al, 2009;Volkert & Vaz, 2010). It has been reported that children with ASD exhibited adherence to sameness during mealtimes (Ahearn et al, 2001;Koegel et al, 2012).…”
Section: (American Occupational Therapy Associationmentioning
confidence: 97%
“…The findings have shown that children with ASD were more likely to exhibit restrictive and inflexible eating behaviors, eat continually throughout the day instead of during specific mealtimes, resist sitting at the table, and throw or dump food during mealtimes compared to children who are typically developing (Koegel et al, 2012;Matson et al, 2009;Volkert & Vaz, 2010). It has been reported that children with ASD exhibited adherence to sameness during mealtimes (Ahearn et al, 2001;Koegel et al, 2012).…”
Section: (American Occupational Therapy Associationmentioning
confidence: 97%
“…A number of studies have shown the effectiveness of behavioral interventions for increasing acceptance of new foods [15,16,96]. However, there are only a few studies demonstrating that acceptance of new foods generalizes to other foods or other environments and that preferences of the child have been taken into account [97,98].…”
Section: Behavioral Treatment Approachesmentioning
confidence: 99%
“…Physical guidance and non-withdrawal of the spoon are the general methods used for this situation [15]. The spoon is presented to the child and kept near his mouth until the food is accepted.…”
Section: Behavioral Treatment Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the time, one of the parents recognizes a self characteristic in their child; "I also don't like yoghurt with pieces of fruit", or "I don't like vegetables either". At the other end of the spectrum, the very severely restricted feeding disorder usually requires intensive treatment in an outpatient setting or an inpatient treatment for several weeks/months [7] [8]. However, this intensive treatment is not available or suitable for every child.…”
mentioning
confidence: 99%